2022
DOI: 10.1155/2022/7941374
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/Calmodulin-Dependent Protein Kinase II Regulation by Inhibitor of RIPK3 Protects against Cardiac Hypertrophy

Abstract: The activity of Ca2+/calmodulin-dependent protein kinase II δ (CaMKII δ) is central to the mechanisms of cardiovascular diseases. Receptor-interacting protein kinase 3- (RIPK3-) mediated necroptosis has been reported to contribute to cardiac dysfunction. However, the potential protective role of inhibition of RIPK3, a regulator of CaMKII, on cardiac hypertrophy remains unclear. The present study is aimed at investigating how the RIPK3 inhibitor GSK’872 regulates CaMKII activity and exploring its effect on hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
(68 reference statements)
0
0
0
Order By: Relevance
“…The clinical manifestations of HCM include palpitations, exertional dyspnea, precordial pain, syncope, HF or even sudden death, and HCM is one of the main causes of sudden cardiac death in young adults ( 105 ). A growing body of evidence has suggested that necroptosis is also involved in the development of cardiac hypertrophy and HCM ( 22 , 23 ).…”
Section: Effects Of Ripk3-camkii-mptp Signaling Pathway Activation In...mentioning
confidence: 99%
See 4 more Smart Citations
“…The clinical manifestations of HCM include palpitations, exertional dyspnea, precordial pain, syncope, HF or even sudden death, and HCM is one of the main causes of sudden cardiac death in young adults ( 105 ). A growing body of evidence has suggested that necroptosis is also involved in the development of cardiac hypertrophy and HCM ( 22 , 23 ).…”
Section: Effects Of Ripk3-camkii-mptp Signaling Pathway Activation In...mentioning
confidence: 99%
“…Previous studies have demonstrated that CaMKII expression was increased in cardiac hypertrophy and have also revealed that the regulation of CaMKIIδ alternative splicing may be related to cardiac function and was involved in cardiac hypertrophy in humans and mice ( 74 , 106 , 107 ). In a recent animal study, a murine model of HCM was constructed by subcutaneous infusion of angiotensin II using osmotic minipumps ( 22 ). The study revealed that, compared with those in the mice without myocardial hypertrophy (infusion of phosphate buffered solution), the levels of RIPK3 in HCM mice were markedly increased, and the levels of both the oxidation and phosphorylation of CaMKIIδ were also increased ( 22 ).…”
Section: Effects Of Ripk3-camkii-mptp Signaling Pathway Activation In...mentioning
confidence: 99%
See 3 more Smart Citations